KELOMPOK PEMUDA DALAM ANTISIPASI BAHAYA NARKOTIKA MELALUI PENDEKATAN HOLISTIC DI KELURAHAN PANGKALAN JATI BARU KECAMATAN CINERE KOTA DEPOK - Mulyadi Mulyadi; Kayus Lewoleba; Satino Satino; Robiah Adawiyah; Fallen Annisa Aji Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Pangkalan Jati area is located in the north of the city of Depok and borders the province of DKI Jakarta and is included in one of the Cinere districts, the hustle and bustle of Depok city life has an impact especially on people's lives. youth, population density will affect people's lives, with the high activity of the emergence of problems in society, including youth activities in association, the vulnerability of youth in promiscuity today, not a few young people are affected by negative associations. , associations that lead to the use of illegal drugs, namely narcotics, especially in and around the Depok City area. Community Service Activities (PKM) are carried out using methods, counseling and face-to-face interactive dialogue with the theme